2000-2009 the decade that changed the world - Sullivan, Robert (LIFE Books/Time Inc., 2009)
The editors at LIFE vigorously carry on the traditions of excellence in photography, in journalism, and in telling the story of our country and our world which began with LIFE magazine in 1936 by founding editor and publisher, Henry R. Luce. They have published books on a broad range of subjects, including New York Times bestsellers One Nation